Jual-Beli Emas Non-Tunai: Fatwa DSN-MUI, Pandangan Ulama’ Klasik dan Modern - Arifin, Bustanul; Nisa, Himmatun (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. The value of gold remains one of the long-term investment oions. Meanwhile, the scholars (Fuqaha) tend to have the opposite view of gold investment.Aim. Studying the legal aspects of buying and selling gold on a non-cash basis according to the views of classical and modern Fuqaha.Methods. The study analyzed the sale and purchase of non-cash gold qualitatively with three stages of descriive methods, namely descriion, formulation and interpretation.Results. Classical scholars tend to forbid the law of buying and selling gold in non-cash based on the idea that gold is a medium of exchange. Modern scholars tend to allow the sale and purchase of gold non-cash based on the consideration that gold is currently a commodity (goods that can be traded) not a medium of exchange. Islamic law is experiencing the development of the cause of illat (the legal reason that includes the law that appears has disappeared).